Hubungan Perilaku Konsumsi Zat Besi dengan Kejadian Anemia pada Ibu Hamil di Klinik Bidan Norma Tahun 2023 - Dea Ardyati; Sri Rezeki (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Apart from being caused by poverty in which nutritional intake is very poor, anemia in pregnant women can also be caused by gender inequality and ignorance about correct eating patterns. Iron deficiency results in a deficiency of hemoglobin (Hb). The aim of the research was to determine the relationship between knowledge about anemia and consumption of iron tablets in pregnant women at the Midwife Norma Clinic in 2023.The type of research carried out was Descriptive Analytical with a cross sectional approach, the population in the study was 53 people using a Random Sampling System. The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used is chi square.The results of the cross-tabulation research showed that the majority of the measures of low iron consumption were 21 (61.8%) respondents who experienced anemia and the minority of good consumption measures were 2 (5.8%) respondents who experienced no anemia with the Chi-Square showing a p value of 0.000. So Ho is rejected and Ha is accepted, which means there is a relationship between the action of consuming iron and the relationship between knowledge about anemia and consumption of iron tablets in pregnant women at the Norma Midwife Clinic in 2023.The conclusion is that all health workers at the Midwife Norma Clinic are expected to be more active in looking at iron consumption and the incidence of anemia in pregnant women. Keywords: Iron Consumption Behavior, Anemia in Pregnant Women